The Color of Knowledge: Impacts of Tutor Race on Learning and Performance - Vojtech Bartos; Ulrich Glogowsky; Johannes Rincke (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We demonstrate that racial biases against tutors hinder learning. In e-learning experiments, U.S. conservatives are more likely to disregard advice from Black tutors, resulting in reduced performance compared to learners taught by white tutors. We show that the bias is unconscious and, consequently, does not skew tutor selection. In line with our theory, the bias disappears when the stakes are high. In contrast, liberals favor Black tutors without experiencing learning disparities. Methodologically, we contribute by using video post-production techniques to manipulate tutor race without introducing typical confounds. Additionally, we develop a novel two-stage design that simultaneously measures tutor selection, learning, and productivity.
Keywords: C90; D83; D91; J71; 330; discrimination; racial bias; learning; online experiment